The Effectiveness of Emotional Schema Therapy on Executive Functions in Adolescents with Emotional Dysregulation in Isfahan - Prande, Leila; Malekian, Azadeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to investigate the effectiveness of Emotional Schema Therapy on the executive functions of adolescents with emotional dysregulation. Materials and Methods: This study employed a quasi-experimental design with a pretest–posttest control group. The statistical population consisted of middle and high school students in Isfahan during 2025 who had been referred to educational counseling centers. The sample included 30 adolescents selected through purposive sampling from individuals with low emotion regulation scores and randomly assigned to an experimental group and a control group (15 participants in each group). The research instruments included the Executive Functions Questionnaire and the Difficulties in Emotion Regulation Scale. The experimental group received Emotional Schema Therapy in twelve 60-minute sessions. Data were analyzed using Multivariate Analysis of Covariance (MANCOVA). Findings: The results indicated that after the intervention, there was a significant difference between the experimental and control groups regarding the dimensions of executive functions (p < .01). Specifically, executive functions improved in the experimental group. Conclusion: The findings suggest that Emotional Schema Therapy is effective in improving the cognitive-behavioral components of adolescents with emotional dysregulation. This therapeutic approach may serve as an effective intervention in counseling and treatment programs for adolescents.